Improvement on moisture content and soil permeability of alfisol soil using organic materials and vesicular arbuscular mycorrhizae (VAM) as planting medium of maize - Akhsin Zulkoni (UNIVERSITAS PEMBANGUNAN NASIONAL ”VETERAN” YOGYAKARTA, 2014)
Maize (Zea mays, L.) is one type of plant included in family Graminaceae. The fibrous roots require soil nests so that it becomes easier for root penetration. Benefits of organic material and Vesicular-Arbuscular-Mycorrhizae (VAM) on the growth of maize obtained through its influence on improvement of soil physical properties. The study of efforts to increase moisture levels and permeability of soil organic matter on Alfisol soil using VAM aims to find the best formula between the dose of organic material and the VAM inoculation to improve Alfisol physical properties. Experiment arranged in a randomized complete block design with three replications. The first factor was a dose of organic manures, including 0 tons ha-1 (B0), 20 tons ha-1 (B1), 40 t ha-1 (B2), and 60 tons ha-1 (B3). The second factor was inoculation VAM, which were no inoculation (J0) and with VAM inoculation (J1). Soil moisture level was analyzed using Gravimetri methods and soil permeability was analyzed using a permeameter. The data subjected to analysis of variance followed by Least Significant Difference (α: 5%).The results showed that the application of organic manures 40 tons ha-1 in combination with inoculation VAM is the best treatment for improving soil physical properties. Soil moisture levels reached 15.72%, increased 7.32% from the control levels of 8.40%. Similarly, permeability land rose from 0.51 cm s-1 to 1.38 cm s-1. Provision of organic matter and inoculation VAM cause for the better soil structure, increasing water holding capacity, and the ability of the soil to pass water easily.Keywords: soil moisture levels keringangin, permeability, organic matter, VAM